Polimorfismo BSMI (RS 1544410) na expressão do gene do receptor da vitamina D e sua relação com a auto declaração de cor da pele - Retamoso, Vanessa Rosa (2023)
Introduction: Hypovitaminosis D has been observed in different populations, especially in white Europeans and Americans, but there are still few studies that associate the decrease of this vitamin in black populations, becoming a concern for public health. Vitamin D levels can be influenced by environmental factors such as diet, as well as by genetic factors such as polymorphisms and gene expression. Objective: To investigate the influence of the BSMI polymorphism of the vitamin D receptor gene (VDR) on serum vitamin D levels, VDR gene expression, CYP24A1 and SOD2, food consumption and self-declaration of race/color in Fronteira Oeste-RS. Methods: The study was approved by CEP-UNIPAMPA (nº977827). The participants were invited in the community (Uruguaiana and São Borja) and, after accepting and signing the TCLE, they responded to a follow-up followed by identification data, self-declaration of race/color, nutritional data (FFQ and 24hR). Blood collection for biochemical analyzes was performed in fasting and vitamin D was measured by chemiluminescence, polymorphism analysis was performed by real-time PCR and gene expression was conducted by qRT-PCR, using QuantiFast SYBR® Green PCR Master Mix. Data were plotted on an Excel spreadsheet and analyzed using a statistical program. Data were presented as mean ± SD and frequencies, Student's t test, chi-square and one-way ANOVA, performed for analysis of differences between groups, and p≤0.05 was considered significant. Results: 114 subjects participated in the study, 56.1% female with a mean age of 30.5 ± 10.6 years. A comparison was made between the averages and later evaluations through color stratification. Vitamin D levels are significantly reduced in blacks (15.93ng/dL±4.58) when compared to browns and whites (p=0.024). There was no statistically significant difference for dietary intake of vitamin D between groups (p=0.479), and again the lowest consumption is among blacks (0.93mcg±1.19). The genotype frequency was GG (43%), GA (40.4%) and AA (16.7%). And in a second moment, all participants with hypovitaminosis D (98 individuals) vitamin D <20ng/dL were selected and the expression of 3 other genes was evaluated: VDR, CYP24A1 and SOD2, where the BsmI SNP of the VDR gene showed overexpression of CYP24A1 and low expression of SOD2. Conclusion: The serum levels of vitamin D observed in the groups, as well as the dietary intake of vitamin D source foods, are insufficient and arouse concern. And in a logistic regression model, it can be observed that the self-declaration of skin color as “black” constituted a risk factor for low serum levels of vitamin D, in addition to verifying that the SNP Bsm I of the VDR gene can modulate gene expression without interfering in serum levels.